1988
DOI: 10.2134/agronj1988.00021962008000040024x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Water‐Use Efficiency, and Digestibility of Crested, Intermediate, and Western Wheatgrass

Abstract: Relationships between dry matter distribution among plant components, growth rates, in vitro digestible organic matter (IVDOM), and water-use efficiency (WUE) have not been defined for cool-season wheatgrass species grown on the Northern Great Plains. Three cultivars each of crested wheatgrass (Agropyron desertorum (Fisch. ex Link) Schult.}, intermediate wheatgrass (Elytrigia intermedia (Host) Nevsk: Syn: A. intermedium (Host) Beauv.}, and western wheatgrass (Pascopyrum smithii (Rhdb.) LOve Syn: A. smithii Ryd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Western wheatgrass, native to North America, is generally considered less productive than introduced species of the Triticeae tribe (Schuster and de Leon Garcia, 1973; Frank and Karn, 1988; Asay et al, 2001). However, there are examples in which production from western wheatgrass was equal to or greater than production from intermediate wheatgrass (Launchbaugh, 1958; McGinnies et al, 1963), tall wheatgrass (Holechek et al, 1989), or Russian wildrye (Newell and Keim, 1947).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Western wheatgrass, native to North America, is generally considered less productive than introduced species of the Triticeae tribe (Schuster and de Leon Garcia, 1973; Frank and Karn, 1988; Asay et al, 2001). However, there are examples in which production from western wheatgrass was equal to or greater than production from intermediate wheatgrass (Launchbaugh, 1958; McGinnies et al, 1963), tall wheatgrass (Holechek et al, 1989), or Russian wildrye (Newell and Keim, 1947).…”
Section: Resultsmentioning
confidence: 97%
“…In June, IVDDM concentration was similar among grass species for all years except 2000 when intermediate wheatgrass was lower than the other three grasses. White and Wight (1981) found Russian wildrye had higher IVDDM than intermediate wheatgrass in 3 of 8 yr while Frank and Karn (1988) reported higher in vitro digestible organic matter concentration in intermediate wheatgrass relative to western wheatgrass.…”
Section: Resultsmentioning
confidence: 99%
“…Although root production is greater in warm vs cool climates, root biomass is often greater in the latter due to reduced turnover which is a function of temperature (Redmann 1975, Sims andCoupland 1979). Root turnover on the mixed prairie was estimated to be 18% (Sims and Coupland 1979) while 62% of Ihe roots were functional in a blue grama communiry (Singh and Coleman 1974 (Frank and Karn 1988). In another test, crested wheatgrass was more WUE (4.1g kg-'; than wesrern wheatgrass (2.6 g kg -t) which was associated with reduced LAI.…”
mentioning
confidence: 99%
“…This plant originates from an environment of low rainfall (Table 1), therefore, this result may be related to adaptations for limited water availability in the soil in order to increase their persistence in the pasture. Frank and Karn (1988) reported that genotypes with high growth rates are less tolerant to drought. It is noteworthy that the municipality of São Bento do Una has the highest intensity and frequency of droughts among the evaluated sites.…”
Section: Resultsmentioning
confidence: 99%